DECODING SUBTLE DIFFERENCES: THE SEMANTIC AND COLLOCATIONAL PATTERNS OF CLEVER AND INTELLIGENT - Fadhilah Larasanti; Zahroh Nuriah (Elite Laboratory Jurusan Sastra Inggris Universitas Bangka Belitung, 2026)
This study investigates collocational patterns of the words clever and intelligent in English. This study was explored through a qualitative approach. Data from the British National Corpus (BNC) was analyzed using the UCREL Semantic Analysis System (USAS) to identify semantic categories and collocations relationships. The results revealed that clever and intelligent share a high degree of semantic preference similarity, with 16 out of 20 semantic categories overlapping, representing an 80% similarity in meaning domains. However, the remaining four categories were used by only one of the words, which shows that each word also has its own specific areas of use. In addition, from 311 total collocates found in the corpus, only 30 were used by both clever and intelligent. These findings suggest that while clever and intelligent are close synonyms sharing broad semantic preferences, the two are not completely interchangeable.